Implementasi Classical Conditioning dalam Pembelajaran PAI - Baharuddin Baharuddin (TADRIS: Jurnal Pendidikan Islam, 2020)
SMAN 1 Teladan Yogyakarta in learning Islamic religious education uses behavioristic theory known as classical conditioning. This study aims to determine the implementation of classical conditioning in the learning of Islamic religious education at SMAN 1 Teladan Yogyakarta and the factors that influence it. This study supports qualitative research with a case study approach. Data collection is done by using observation and interview methods. The results of the study showed that the application of classical conditioning in PAI learning was carried out through several stages, namely (1) making the classroom atmosphere comfortable. The stages carried out are giving freedom to students in expressing opinions during discussions, tucking in intermezo in the explanation of the material, occasionally using English in the explanation of the material, and the use of LCD in learning. (2) assigning tasks is continuous. Assignments given in the form of group discussions and cult. Students perform a cult when the teacher prepares teaching material. In addition the stimulus makes students become active in learning. The factors that influence it are the teacher's factor, the teacher has the ability to understand student psychology so that he understands the theory or the right method to use. Student factors, students have a sense of responsibility for the tasks given, and the attitude of complementarity in the cult task. Institutional factors, institutions or schools that support in terms of vision and mission and school policies.